Forecrop Effects on Abundance and Diversity of Soil Microorganisms during the Growth of the Subsequent Crop - Anna Siczek; Magdalena Frąc; Agata Gryta (Agronomy, 2020)
Plant residues introduced into the soil influence the soil’s physical, chemical, and consequently, biological parameters, which have an influence on plant health and yields. This study was undertaken to evaluate the effects of the cultivation of widespread plant species, faba bean (Vicia faba L., F) and wheat (Triticum aestivum L., W) (as forecrops) grown under conventionally tilled fields, on the diversity of microorganisms and the enzymatic activities of soil during the growth of the subsequent wheat. Bulk soil samples (0–20 cm) were taken three times from two months after residue incorporation into the soil to the maturity of the subsequent wheat crop in order to assess the fungal and bacterial communities (Next Generation Sequencing (NGS), terminal restriction fragments lengths polymorphism (t-RFLP)), ammonia oxidizing archaea (t-RFLP, denaturing gradient gel glectrophoresis (DGGE)), and the enzymatic activity of soil. Differences in the genetic structure of ammonia-oxidizing archaea (AOA) were observed for each treatment and sampling term, indicating that plant and weather conditions are the driving force for microorganism selection and adaptation. We observed that the fungal community was more influenced by the forecrop type used than the bacterial community. The activities of the enzymes changed in response to the forecrop and sampling period. A higher number of microorganisms that are associated with plant benefits with respect to nutrients and growth, as well as higher amounts of N in the residues, was noted in faba bean than in wheat soil. This could indicate better growth conditions after faba bean and, consequently, better yield quality and quantity. This may also indicate some protective role of the soil after faba bean against pathogens, which may be connected with lower fungicide requirements. The obtained results lead to a deeper understanding of the microorganism reactions to faba bean and wheat residues during wheat cultivation. In addition, they may be helpful in improving our understanding of subsequent crop yield responses to forecrops.